THE STATUS OF THE TEACHER DURING THE PERIOD OF THE CORONAVIRUS CRISIS AND DISTANCE LEARNING: CHALLENGES, CHANGES, AND TEACHER-PARENT RELATIONS - Winkler, Ram (E-Journal VFU, 2025)
This article discusses the effects of the outbreak of the coronavirus pandemic (2020) and the transition to online learning on the teacher’s status and the teaching challenges in Israel and around the world. The transition to online learning presented the teachers with significant challenges, including dealing with new technologies, mental burnout, and communication challenges with students and their parents. The research used the qualitative approach, with the goal to examine the experiences of teachers in secondary school education in the crisis period. The findings indicate that the teachers were required to adjust rapidly to the new conditions, while dealing with systemic requirements, management of emotional loads, and lack of uniformity in the level of professional support they received. The research conclusions emphasize the need to shape an adjusted educational policy, the goal of which is to strengthen the teachers’ status, improve the professional support, and develop skills of teaching suited to the digital era.